Match-related performance during the Olympic Games 2020: a technical variability analysis of high-level judo athletes - Kons, R. L. Agostinho, M. F.; Santos, D. F. C.; Lopes-Silva, J.; Detanico, D.; Franchini, E. (International Journal of Performance Analysis in Sport, 2022)
This study aimed to identify the technical-tactical variation through the index of performance and types of techniques in high-level judo in the 2020 Olympic Games. The data were extracted from the Official Results Books considering the competition performance of 393 competitors. Nage-waza katame-waza and scoring index, and the classification of techniques groups according to the sex, weight category and competition outcome were analysed. A t-test was used to compare the variables according to the sex and analysis of variance to compare weight categories and competition outcome groups. Finally, the Chi-square tests were used to test the association between frequency of groups of techniques and places in the competition, weight category and competition outcome. The level of significance is 5%. The main results demonstrated higher nage-waza and katame-waza variation (absolute values) for medallist compared to the other groups (p < 0.001), and higher values for repechage group compared to the non-medallist (p < 0.001). The katame-waza variation index was higher in female (p = 0.019) and medallists have a higher scoring and nage-waza variation index compared to the repechage group and non-medallist (p < 0.001). We concluded that medallist athletes have high technical variability compared to the other groups and female athletes have a high katame-waza variation compared to the male.